2005
DOI: 10.1038/nn1432
|View full text |Cite
|
Sign up to set email alerts
|

Persistent hippocampal CA1 LTP in mice lacking the C-terminal PDZ ligand of GluR1

Abstract: The C-terminal PDZ ligand of the AMPA receptor GluR1 subunit may be important for expression of CA1 hippocampal long-term potentiation. To test this directly in vivo, we generated a knock-in mouse lacking the last seven residues of GluR1, comprising the PDZ ligand. This deletion did not affect basal GluR1 synaptic localization, basal synaptic transmission, long-term potentiation or long-term depression, indicating that the ligand is not required for CA1 hippocampal synaptic plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 12 publications
8
89
0
Order By: Relevance
“…However, as discussed below, this model has been challenged by several recent reports. These include reports interrogating the roles in activity-dependent trafficking and synaptic plasticity of specific AMPAR subunits 18,19 , their C-terminal tails and PDZ ligands 20,21 and changes to their phosphorylation status 22 . Taken together these findings have initiated a reappraisal of the core mechanisms underlying synaptic incorporation of AMPARs.…”
Section: Subunit-specific Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as discussed below, this model has been challenged by several recent reports. These include reports interrogating the roles in activity-dependent trafficking and synaptic plasticity of specific AMPAR subunits 18,19 , their C-terminal tails and PDZ ligands 20,21 and changes to their phosphorylation status 22 . Taken together these findings have initiated a reappraisal of the core mechanisms underlying synaptic incorporation of AMPARs.…”
Section: Subunit-specific Traffickingmentioning
confidence: 99%
“…The direct role of GluA1 interactors in promoting synaptic incorporation of CP-AMPARs is largely unclear. Indeed, while early studies reported the requirement for the GluA1 PDZ ligand in mediating insertion of GluA1-containing AMPARs during LTP 16 , this observation has been called into question by the generation of knock-in mice lacking the final 7 C-terminal residues of GluA1, including the PDZ ligand 20 . At CA1 hippocampal synapses, neither localization of GluA1 nor LTP or LTD were altered by deletion of the GluA1 PDZ ligand.…”
Section: Mechanisms Of Subunit-specific Traffickingmentioning
confidence: 99%
“…PSD-MAGUKs generally interact with AMPARs through AMPAR auxiliary subunits known as transmembrane AMPAR regulatory proteins (TARPs), which have PDZ-binding motifs (29). SAP97 is alone among the PSDMAGUKs in interacting directly with AMPAR subunits, namely GluA1 (20,23). Some reports show that germline knockout of any single PSD-MAGUK family member, PSD-93, PSD-95, or SAP 102, causes no major disturbance in glutamatergic synaptic transmission (7,15,30, but see 9, 28).…”
Section: Deletion Of Sap97 Does Not Alter Synaptic Transmission and Lmentioning
confidence: 99%
“…SAP97β directly binds to AMPAR GluA1 subunits (20)(21)(22)(23). Because SAP97 has been resistant to RNAi in our hands (but see 10) and germline KO causes lethal feeding deficits in neonatal mice (24), SAP97's synaptic function is uncertain and is based primarily on dissociated neuronal culture studies.…”
mentioning
confidence: 99%
“…A model was proposed according to which LTP activates CaMKII, which then phosphorylates GluR1 and a protein that binds to the PDZ domain of GluR1 Shi et al, 2001). However, the role of the PDZ binding domain in the trafficking of GluR1 is still controversial (Kim et al, 2005). A recent study showed the delivery of a recombinant cytosolic GluR1 C-terminal fragment to the PSD after induction of LTP, and synaptic incorporation of this construct was sufficient to allow spine enlargement (Kopec et al, 2007).…”
Section: Role Of Ampars In Ltpmentioning
confidence: 99%